Hubungan antara Persepsi dan Sikap Ibu dengan Female Genital Mutilation di Desa Sei Suka, Sumatera Utara pada Tahun 2024 - Ariska Fauzianty; Maya Nurdiyanti; Nova Isabella Mariance Br Napitupulu (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Globally, at least 100 million girls are at risk of undergoing female genital mutilation (FGM) each year, with an estimated 6,000 girls affected every day. In Indonesia, the practice of FGM is generally rooted in cultural or traditional beliefs that have been passed down through generations within communities. Therefore, this study aims to examine the relationship between mothers' perceptions and attitudes and the practice of female genital mutilation (FGM). This is a quantitative study employing a cross-sectional design. Data were collected using purposive sampling, with a total of 50 participants. Data were analyzed using the Chi-square test. The results showed that Nearly most of the mothers with a positive attitude practiced female genital mutilation (FGM), totaling 12 individuals (80%), and the majority of mothers with poor perception also practiced FGM, totaling 31 individuals (67.4%). The Chi-Square test showed p-values of 0.019 and 0.012, indicating a statistically significant relationship between mothers' perceptions and attitudes and the practice of FGM. It is recommended to provide counseling and health education about female circumcision, with regular evaluations to ensure the information is well understood. These efforts can be carried out through activities at Puskesmas or other healthcare service points, including continuous home visit programs.